Clinico-hematological and immunophenotypic profile of acute leukemia of ambiguous lineage: A four year experience from a single tertiary care centre of West India - Varnika Rai; Beena Brahmbhatt; Anurag Saha; Immanuel P. Thayakaran (Indian Journal of Pathology and Microbiology)
Background: Acute leukemia of ambiguous lineage (ALAL) is a heterogeneous group of rare leukemias that lacks definite evidence of differentiation along one lineage. It includes acute undifferentiated leukemia and mixed-phenotype acute Leukaemia (MPAL). Aims: The present study highlighted the clinicohematological and immunophenotypic profile of ALAL cases diagnosed in the tertiary care centre of western India. Study Design: Retrospective observational study. Methods and Materials: Patients diagnosed with acute leukemia, preferably their bone marrow aspirate samples, were collected in ethylene diamine tetra-acetic acid-vial. The immunophenotypic study was done using the Fluorescence Activated Cell Sorting (FACS) Canto Eight color flow cytometer and a broad panel of monoclonal antibodies. The patients were diagnosed for ALAL, based on the World Health Organization (WHO) 2017 classification. Statistical Analysis Used: Descriptive statistics with categorical and continuous variables. Results: Overall incidence of ALAL was about 2.1%, and singly MPAL and AUL were 1.8%, and 0.3%, in frequency, respectively. The age range was 4 to 57 (median age 21 years), of which 11 (57.9%) were adults and eight were children (42.1%). There was male predominance with Male: Female ratio of 5.3:1. On immunophenotyping, B/myeloid MPAL (42.1%) was the commonest among the ALAL. Translocation t(9;22) was the most common cytogenetic abnormality found mainly in B/myeloid MPAL. Two cases were of chronic myeloid leukemia in a mixed phenotypic blast crisis. Over all prognosis of ALAL was poor. Conclusion: ALAL is overall associated with poor prognosis as both their diagnosis and treatment decisions are difficult owing to the lack of optimum treatment data and the rarity of the disease. Hence, A careful diagnosis with the help of immunophenotyping is crucial.